Supply chain integration, firm characteritics and performance: A study of Malaysian manufacturing firms - Sundram, Veera Pandian Kaliani; Othman, Akmal Aini; Ghapar, Farha Abdol; Battour, Muhamed; Bhatti, Muhammad Awais (2013)
Purpose: The purpose of this study is to investigate on how supply chain integration can influence performance gains for firms in a supply chain management context primarily in the manufacturing industry in a developing country, Malaysia.Design/Methodology/Approach: The study applies survey method and data is collected through questionnaire composed of dimensions of supply chain integration, firm performance and firm characteristics.Data is collected from 50 respondents, from manufacturing firms across Malaysia.The collected responses were analysed using descriptive analysis and multiple regression.Findings: Based on the firm-level data, the study found that supply chain integration generates significant and sustainable performance gains.This implies that due to the limited capability of manufacturers in developing countries in practicing higher order supply chain capability, these lower order supply chain integration played an important role. Interestingly, among the three different types of integration, the informational integration has a greater impact on performance.Research Limitations / Application: The sample consisted logistics managers, supply chain managers and operational manager with vast operational experiences.There is only one respondent from each firm and as such this opens for response bias.Practical Implication: It is important for both managers and policy makers to place specific attention to informational integration.This study further draws managerial and policy implications and offers lessons for other developing countries. Originality/ Value: The research is an original contribution to the body of knowledge as this study develops a model to investigate the impact of three different forms of supply chain integration namely financial, physical and information flow integration on firms’ performance.